An investigation on mandibular radiometric indices in normal female population referred to maxillofacial radiology centers in Rasht. - Dalili Z. Assistant Professor. Moghadam Qujeq A. Dentist (Tehran University of Medical Sciences, 2003)
Statement of Problem: Bone material density (BMD) is significantly decreased among postmenopausal women leading to the most common metabolic disease, osteoporosis."nMultiple bone fractures are of the most important consequences of this disease, which cost too much for the"nsociety. One of the cheapest and most available methods for the diagnosis of bone density changes is bone"nradiomorphometric evaluation by conventional methods. Studies have also revealed that mandibular"nradiomorphometric indices in panoramic radiographs yield invaluable information, which can be used as a"nscreening method to diagnose patients with decreasing bone density, and to determine normal values of"nmandibular radiomorphometric indices among normal subjects in different populations."nPurpose: The aim of the present study was to investigate the mandibular radiomorphometric indices in"npanoramic radiographs among normal female population referring to maxillofacial radiology centers to"ndetermine their relationship with age and the total teeth number of the subjects under study."nMaterial and Methods: In this descriptive-analytic study, two mandibular radiomorphometric indices namely"nthe Antegonial quantitative index (AI) and the Cortical qualitative index (MCI) were evaluated on 417"npanoramic radiographs of a female normal population, aged more than 20 years which divided into five age"ngroup, by one maxillofacial radiologist as an observer. The relationship between these indices, and also with"nthe number of teeth and age were investigated by variance and Pearson's analysis."nResults: Mean quantitative index (AI) was 3.54±54%mm. The prevalence of MCI index was C2: 71.5%,"nCI: 20.9%and C3: 7.7%. There was significant correlation between AI/MCI indices with age, dentition and"nalso with each other.(P<0.0001)."nConclusion: Based on the present study, with increasing age the mean AI and the number of teeth decrease"nsignificantly. MCI index also shows higher porosity in mandibular cortex (C3 index). Therefore, Mandibular"nradiomorphometric indices are useful in initial diagnosis and screening of patients with low bone mineral"ndensity (osteopenia, osteoporosis).